2012
DOI: 10.1155/2012/549782
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sliding Mode Control Technique for Indirect Current Controlled Active Power Filter

Abstract: A novel sliding mode control (SMC) method for indirect current controlled three-phase parallel active power filter is presented in this paper. There are two designed closed loops in the system: one is the DC voltage controlling loop and the other is the reference current tracking loop. The first loop with a PI regulator is used to control the DC voltage approximating to the given voltage of capacitor, and the output of PI regulator through a low-pass filter is applied as the input of the power supply reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…In other words, it changes the DCC-based operation to ICC-based operation. Unlike DCC-based operation, ICC-based operation which has been reported in [43][44][45]47] to possess exact information on switching ripples existing in the source current, allows accurate generation of reference currents to continuously control the operation of the SAPF and thus eliminates any unnecessary problem caused by SAPF switching operations.…”
Section: Proposed Simplifications and Refinementsmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, it changes the DCC-based operation to ICC-based operation. Unlike DCC-based operation, ICC-based operation which has been reported in [43][44][45]47] to possess exact information on switching ripples existing in the source current, allows accurate generation of reference currents to continuously control the operation of the SAPF and thus eliminates any unnecessary problem caused by SAPF switching operations.…”
Section: Proposed Simplifications and Refinementsmentioning
confidence: 99%
“…To date, the conventional STF-pq theory algorithm still produces a non-sinusoidal reference current [7,40,42] and thus forces the SAPF to operate based on a direct current controlled (DCC) scheme [43][44][45]. From previous literature [45][46][47], it is revealed that the SAPF switching operation produces switching ripples which potentially degrade the THD value of the mitigated source current.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the conventional SRF algorithm is still producing a non-sinusoidal reference current through a derivation of the extracted harmonic current, and forcing the switching signals meant for controlling the switching activities of the SAPF to be generated based on the direct current controlled (DCC) scheme [30]- [32].…”
Section: Introductionmentioning
confidence: 99%